Of Sea Lice and Superfood: A Comparison of Regional and National News Media Coverage of Aquaculture - Rickard, Laura N.; Feldpausch-Parker, Andrea Marie (Frontiers in Communication, 2016)
As wild fisheries decline, aquaculture, or the cultivation of species in fresh and salt water, will provide the majority of seafood consumed worldwide. Given that aquaculture is an increasingly critical food “technology” – with implications for public opinion formation – we apply theory of social function systems and sustainability to a U.S. news media content analysis. We examine coverage of aquaculture (N = 493 articles) over a ten-year period (2005-2015), comparing four regional and four national newspapers for discussion of risks, benefits, science, economics, political/legal issues, and environmental sustainability. Results suggest the dominance of risk in regional and national news; however, we also find more recent attention to benefit and sustainability. Differences within and between regional and national newspaper coverage further suggest that the conversation about aquaculture varies within the U.S., is multi-dimensional, and involves frequent co-occurrence